Incidence and risk factors of esophagogastric varices bleeding in cirrhotic patients with advanced hepatocellular carcinoma treated with lenvatinib. (March 2023) - Iavarone, M.; Alimenti, E.; Tada, T.; Shimose, S.; Suda, G.; Yoo, C.; Soldà, C.; Piscaglia, F.; Casadei-Gardini, A.; Marra, F.; Vivaldi, C.; Conti, F.; et al.
Abstract : Background and aims: Lenvatinib is indicated for the forefront treatment of advanced hepatocellular carcinoma (aHCC) but its use it is eventually limited by presence of esophagogastric varices (EGV) and bleeding-risk. This study aimed to assess prevalence and risk factors of EGV and bleeding in lenvatinib-treated patients with HCC. Methods: In this multicenter international retrospective study, cirrhotic patients treated with lenvatinib for aHCC with an upper-gastrointestinal endoscopy performed <6 months before treatment were enrolled. Primary endpoint: incidence and risk factors of EGV bleeding during treatment. Secondary endpoints: prevalence and risk factors for EGV and high-risk EGV (HR-EGV) at baseline. Results: 535 patients were enrolled [median age 72 years, 78% male, 63% viral aetiology, 89% Child-Pugh-A, 16% neoplastic portal vein thrombosis (nPVT), 56% BCLC-C]: 301 (56%) patients were EGV-free, 234 had EGV (44%) and 70 (30%) HR-EGV. Presence of EGV and of HR-EGV were independently associated with Child-Pugh-B (OR 2.12; 95%CI 1.08-4.17, p=0.03), nPVT (OR 2.54; 95%CI 1.40-4.61, p=0.002) and platelets<150.000/uL (OR 2.47; 95%CI 1.35-4.50, p=0.003). During lenvatinib treatment, 17 patients bled from EGV, the 12-month cumulative incidence being 3%. The only independent predictor of bleeding was presence of HR-EGV (HR 6.94, 95% CI 2.23-21.57, p=0.001). Risk of EGV bleeding can be stratified according to Child-Pugh-B, presence of nPVT and platelets<150.000/uL into low (0/3 risk factors, 6-months cumulative incidence 0.77%), intermediate (1/3 risk factors, 6-months cumulative incidence 2.31%) and high (2/3 or 3/3 risk factors, 6-months cumulative incidence 7.40%). Among the 476 Child-Pugh-A patients, independent predictors of HR-EGV were nPVT (OR 2.53; 95%CI 1.24-5.16, p=0.008) and platelets<150.000/uL (OR 2.56; 95%CI 1.28-5.10, p=0.01). Conclusion: In HCC patients treated with lenvatinib, the risk of EGV bleeding is low but it increases in patients with HR-EGV at baseline. A risk stratification for HR-EGV can be applied according to liver reserve, platelet count and nPVT.